Modelling and analysis of e-mail management for improved customer relationship management. (31st August 2005) - Greve, Robert A.; Sharda, Ramesh; Kamath, Manjunath; Kadam, Amit
Customer contact centres represent a growing industry in which Customer Relationship Management (CRM) applications have been developed and used successfully. Customer call centres, a multi-billion dollar industry, are evolving into customer contact centres, which now include channels of communication other than the telephone. E-mail, a popular alternative to the telephone for all types of communication, is becoming a common medium for customer contact. CRM applications currently exist that allow us to implement and monitor e-mail management strategies. For example, incoming e-mail can be automatically routed to specific customer service agents according to predefined routing rules. The routing mechanisms available in the software tools are heuristic, and not based upon any scientific analysis of the performance of different routing policy alternatives. The objective of this paper is to study the impact of routing strategies and prioritisation of incoming e-mail messages on CRM objectives of an organisation. We create a model representative of and consistent with e-mail response centres in industry. The process modelled was corroborated by a domain expert. A comprehensive simulation study is conducted to analyse different routing policies and prioritisation options. The results of the simulation study indicate that specific routing strategies and the use of specific priority schemes by the e-mail agent can result in a significant improvement in the response centre's performance, as indicated by average response times and average resolution times of different categories of e-mail messages. Although call centre operations have been studied extensively, this study shows that performance of contact centres needs further investigation because of the greater flexibility that exists in the assignment and scheduling of e-mail processing tasks.